Modification of zirconia ceramics by treating the surface of powerful pulsed ion beams - Vasiljev I. P. Ivan Petrovich; Gyngazov (Ghyngazov) S. A. Sergey Anatolievich; Frangulyan (Franguljyan) Т. S. Tamara Semenovna; Chernyavski (Chernyavskiy) A. V. Aleksandr Viktorovich (2014, 2014)
Title screen